Therapeutic potential targeting podocyte mitochondrial dysfunction in focal segmental glomerulosclerosis - Yuting Li; Jiaojiao Fan; Wenping Zhu; Yujia Niu; Aihua Zhang (Karger Publishers, 2023)
Background：Podocytes are essential components of the glomerular filtration barrier and essential for the proper filtration function of the glomerulus. Podocyte injury under various stress conditions is the primary pathogenesis and key determinant of focal segmental glomerulosclerosis (FSGS) with prominent clinical manifestations of proteinuria or nephrotic syndrome. Summary：Under physiological conditions, a highly coordinated mitochondrial quality control system, including antioxidant defenses, mitochondrial dynamics (fusion, fission and mitophagy), and mitochondrial biogenesis, guarantees the sophisticated structure and various functions of podocytes. However, under FSGS pathological conditions, mitochondria encounter oxidative stress, dynamics disturbances, and defective mitochondrial biogenesis. Moreover, mutations in mtDNA and mitochondria-related genes are also strongly associated with FSGS. Based on these evidences, bioactive agents that function to relieve mitochondrial oxidative stress and promote mitochondrial biogenesis have been proven effective in pre-clinical FSGS models. Targeting the mitochondrial network is expected to provide new therapeutic strategies for the treatment of FSGS and delay its progression to end-stage renal disease (ESRD). Key messages：Mitochondrial dysfunction plays a key role in podocyte injury and FSGS progression. This review summarized recent advances in the study of mitochondrial homeostatic imbalance and dysfunction in FSGS and discussed the potential of mitochondria-targeted therapeutics in improving FSGS and retarding its progression to ESRD.